Evaluation Of Bone Loss In Perimenopausal Diabetic Versus Non Diabetic Women in an Outreach Camp - Manpreet Kaur; Gaganpreet Kaur Gill; Sarbhjit Kaur; Nupur Saini; Simran Dhanoa (GMC Patiala Journal of Research and Medical Education, 2019)
Introduction: Osteoporosis and Diabetes Mellitus are major and growing public health problems particularly among perimenopausal women..[2] This study was conducted to correlate prevalence of osteopenia and osteoporosis in perimenopausal women especially in those with diabetes. Materials and methods: In an outreach camp organised by Department of Obstetrics and Gynaecology, Government Medical College Patiala, the study was performed on 65 perimenopausal women above the age of 45 years, out of which 17 were known cases of Diabetes. Age, BMI, BMD and RBS were measured and compared in Diabetic with Non Diabetic group. Chi square test was applied on the data and used for obtaining the results. Results: Mean SD ages were 65.29±10.49 v/ s 57.72±12.63 in Diabetic v/ s Non Diabetic groups . Weight was 67±12.41 vs 68.8±12.38 in Diabetic and Non Diabetic groups respectively. Mean BMI in Diabetic group was 28.09±4.29 and in Non Diabetic group it was 27.70±4.29. There was a significant difference in bone marrow density between the diabetic and non diabetic group. Mean BMD in Diabetic group was -2.33±0.94 and that in Non Diabetic group it was -1.52+0.54. Conclusion: Osteopenia and osteoporosis both are common in perimenopausal women with osteoporosis being more common in diabetics.